Corruption above state contracting in Colombia (2019)
The purpose of this essay is to analyze the latent phenomenon of corruption in state contracting in Colombia, from a historical framework, definition, causes and how these negatively affect the country and its democracy, regulatory aspects of contracting, and how these impacts harm economic , politically and socially to a country like Colombia., causing insufficient resources, distrust and chaos in the administration and as a consequence affecting Public Expenditure, which is destined for public consumption goods and capital goods, public investment; according to The Bank of the Republic, consequently a reduction of the available budget. However, this is due to the lack of supervision and surveillance of the different polity responsible for the monitoring of social policies and the not-application of the different existing tools aimed at providing advice and transparency in the framework of State contracting in Colombia.